Adequacy Degree between Supply and Demand for Intellectual Capital Information in the Annual Reports in an Emerging Country: The Tunisian Case (Global Journal of Management and Business Research, 2016)
Abstract not found
Keywords: intellectual capital; supply; demand; voluntary information; financial market; annual reports